Anti-tumour activity of canine activated T-cells and cytokine-induced killer cells against canine malignant melanoma in vitro - Luiza Cesar Conti; Sonia Capellero; Lisa Piras; Emanuela Morello; Sabina Iurascu; Jessica Erriquez; Laura Marconato; Luca Aresu; Raffaella De Maria (The Veterinary Journal, 2026)

Exploring the prognostic implications of programmed death-ligand 1 expression in canine nodal lymphoma: Insights from surface membrane expression, transcript amount and plasmatic levels - Alessandra Ubiali; Luiza Cesar Conti; Raffaella De Maria; Paola Emanuela Maria Dall'Ara; Laura Marconato; Roberta Ferrari; Damiano Stefanello; Maria Amati; Luca Aresu; Fulvio Riondato; Valeria Martini (Research in Veterinary Science, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Prenatal exposure to fine particulate matter PM2.5 and small for gestational age: a Bayesian model for area-based data in Milan - Simone Colombara; Rossella Murtas; Sara Tunesi; Alessandra Guglielmi; Antonio Giampiero Russo; Paola Angelini; Serena Broccoli; Marco Monti; Nicola Caranci; Katia Raffaelli; Daniela Fortuna; Paolo Giorgi Rossi; et al. (Environmental and Ecological Statistics, 2025)

In situ sonoporation to enhance the tumour uptake of silicon phthalocyanine and improve PDT effectiveness in a triple negative breast cancer murine model - Martina Capozza; Alberto Mangia; Michela Gagliardi; Rachele Stefania; Francesca Garello; Laura Conti; Enzo Terreno (Journal of Photochemistry and Photobiology B: Biology, 2025)

Thrust fault maturity and coseismic behavior: Insights from the 2022 Mw5.8 Adriatic offshore earthquake - Lorenzo Petracchini; Stefano Tavani; Marco Brandano; Eugenio Carminati; Claudio Chiarabba; Alessia Conti; Roberto Devoti; Paolo Galli; Mimmo Palano; Giuseppe Pezzo; Laura Scognamiglio; Elisa Tinti; et al. (Earth and Planetary Science Letters, 2025)

Immunization of rabbits with nanovenom composed of Dendroaspis polylepis venom and silica nanoparticles: a first in vivo approach - Federico G. Baudou; María Herrera; Mariángela Vargas; Mauren Villalta; Florencia S. Conti; Exequiel Giorgi; Laura Leiva; José María Gutiérrez; Adolfo R. de Roodt; Mauricio de Marzi (Toxicon, 2025)

Cyanophage Infections in a Sponge Intracellular Cyanobacterial Symbiont - Tzipora Peretz; Esther Cattan‐Tsaushu; Chiara Conti; Benyamin Rosental; Laura Steindler; Sarit Avrani (Environmental Microbiology, 2025)
Sponges are sessile animals that play crucial roles in marine ecosystems by facilitating nutrient cycling, enhancing biodiversity, and structuring benthic habitats. Microbial symbionts, including cyanobacteria, are vital to sponges, aiding in nutrient cycling, metabolism, and defence. However, due to the sponge's ability to concentrate phages from seawater, extracellular sponge symbionts are particularly vulnerable to phage infection. By contrast, little is known about the susceptibility of intracellular sponge symbionts to phage predation. Here, we present evidence that Candidatus Synechococcus feldmannii, a facultative, horizontally transmitted cyanobacterial endosymbiont of the sponge Petrosia ficiformis , is susceptible to cyanophages. We analysed four Ca. S. feldmannii genomes and found evidence for phage interactions in two, including CRISPR spacers matching sipho‐ and T4‐like cyanophages. One genome harboured a prophage region resembling freshwater cyanobacterial prophages, featuring conserved regions associated with Type VI secretion systems, similar to Wolbachia endosymbionts prophages. Additionally, we developed a method for isolating cyanophages directly from purified sponge bacteriocytes (specialised sponge cells harbouring symbionts) and identified nine T4‐like cyanophages with less than 60% similarity to known relatives. Collectively, our findings indicate that Ca. S. feldmannii is susceptible to cyanophages and suggest potential functional parallels between phages infecting endosymbionts across different animal hosts.

The invasion history of Ambrosia psilostachya (Asteraceae) in Italy: first record and distribution over more than one century - Chiara Montagnani; Rodolfo Gentili; Gerhard Karrer; Sarah Caronni; Alicia Teresa Rosario Acosta; Michele Adorni; Alessandro Alessandrini; Nicola Maria Giuseppe Ardenghi; Gabriella Buffa; Fabrizio Bartolucci; Alessandra Belisario; Fabrizio Bonali; et al. (Plant Biosystems, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Plant Growth-Promoting Yeasts (PGPYs) as a sustainable solution to mitigate salt-induced stress on zucchini plant growth - Chiara Ruspi; Debora Casagrande Pierantoni; Angela Conti; Roberto Scarponi; Laura Corte; Gianluigi Cardinali (Biology and Fertility of Soils, 2025)

The potential mediating role of the gut microbiome and metabolites in the association between PFAS and kidney function in young adults: A proof-of-concept study - Hailey E. Hampson; Shiwen Li; Douglas I. Walker; Hongxu Wang; Qiran Jia; Sarah Rock; Elizabeth Costello; Petter Bjornstad; Laura Pyle; Jonathan Nelson; Frank D. Gilliland; Zhanghua Chen; et al. (Science of The Total Environment, 2024)

Effect of Mitoquinone on sperm quality of cryopreserved stallion semen - Ahmed R. Elkhawagah; Gian Guido Donato; Mariagrazia Poletto; Nicola A. Martino; Leila Vincenti; Laura Conti; Denis Necchi; Tiziana Nervo (Journal of Equine Veterinary Science, 2024)

Soil microbiota resilience in a two-decade long-term experiment comparing an organic and a conventional cropping system - Debora Casagrande Pierantoni; Angela Conti; Laura Corte; Paolo Benincasa; Gianluigi Cardinali; Marcello Guiducci (Applied Soil Ecology, 2024)

Best practices, errors, and perspectives of half a century of plant translocation in Italy - Martina D'Agostino; Luigi Cao Pinna; Marta Carboni; Silvia Assini; Gianluigi Bacchetta; Fabrizio Bartolucci; Lisa Brancaleoni; Fabrizio Buldrini; Angelino Carta; Bruno Cerabolini; Roberta Maria Ceriani; Umberto Clementi; et al. (Conservation Biology, 2024)
Conservation translocations are becoming common conservation practice, so there is an increasing need to understand the drivers of plant translocation performance through reviews of cases at global and regional levels. The establishment of the Italian Database of Plant Translocation (IDPlanT) provides the opportunity to review the techniques used in 186 plant translocation cases performed in the last 50 years in the heart of the Mediterranean Biodiversity Hotspot. We described techniques and information available in IDPlanT and used these data to identify drivers of translocation outcomes. We tested the effect of 15 variables on survival of translocated propagules as of the last monitoring date with binomial logistic mixed‐effect models. Eleven variables significantly affected survival of transplants: life form, site protection, material source, number of source populations, propagation methods, propagule life stage, planting methods, habitat suitability assessment, site preparation, aftercare, and costs. The integration of vegetation studies in the selection of suitable planting sites significantly increased the success of translocation efforts. Although posttranslocation watering had a generally positive effect on translocation outcome, other aftercare techniques did not always increase transplant survival. Finally, we found that how funds were spent appeared to be more important than the actual amount spent. Plant translocations in Italy and in the Mediterranean area should account for the complexity of speciation, gene flow, and plant migrations that has led to local adaptations and has important implications for the choice and constitution of source material.

Expression of miRNA from spent pre-implantation embryos culture media - Claudia Omes; Alice Conti; Laura Benedetti; Veronica Tomasoni; Davide De Marchi; Rossella E. Nappi; M. Gabriella Cusella De Angelis; Gabriele Ceccarelli (Reproductive Biology, 2024)

Strategy for the development of a new stick formula without microplastics - Laura Frigerio; Luigi Padovano; Simone Conti; Miryam Chiara Malacarne; Enrico Caruso (Sustainable Chemistry and Pharmacy, 2024)

Effect of light and feeding regimes on the daily rhythm of thermal preference in Nile tilapia (Oreochromis niloticus) - Gonzalo de Alba; Francesca Conti; Jorge Sánchez; Laura Michelle Godoy; Francisco Javier Sánchez-Vázquez; José Fernando López-Olmeda; Luisa María Vera (Aquaculture, 2024)

The relationship between spectral and plant diversity: Disentangling the influence of metrics and habitat types at the landscape scale - Michela Perrone; Mirko Di Febbraro; Luisa Conti; Jan Divíšek; Milan Chytrý; Petr Keil; Maria Laura Carranza; Duccio Rocchini; Michele Torresani; Vítězslav Moudrý; Petra Šímová; Dominika Prajzlerová; et al. (Remote Sensing of Environment, 2023)

Effect of sow mass vaccination against Mycoplasma hyopneumoniae on the humoral immune response of newborn piglets - Elisa Rigo De Conti; Karine Ludwig Takeuti; Aparecida Tatiane Lino Fiúza; Laura Lopes de Almeida; David Emilio Santos Neves de Barcellos; Fernando Pandolfo Bortolozzo (Tropical Animal Health and Production, 2022)

Unraveling the Lagged Effect of Hydro-meteorological Conditions On the Trophic State of a Reservoir By Applying Dynamic Regression - Pablo F. Andreoni; Marcia A. Ruiz; María Inés Rodríguez; Ana Laura Ruibal-Conti (Water Resources Management, 2022)

IDPlanT: the Italian database of plant translocation - Thomas Abeli; Martina D’Agostino; Simone Orsenigo; Fabrizio Bartolucci; Rita Accogli; Giulia Albani Rocchetti; Claudia Alessandrelli; Arianna Amadori; Filippo Amato; Claudia Angiolini; Silvia Assini; Gianluigi Bacchetta; et al. (Plant Biosystems, 2021)

First application of an Integrated Biological Response index to assess the ecotoxicological status of honeybees from rural and urban areas - Ilaria Caliani; Tommaso Campani; Barbara Conti; Francesca Cosci; Stefano Bedini; Antonella D’Agostino; Laura Giovanetti; Agata Di Noi; Silvia Casini (Environmental Science and Pollution Research, 2021)
Understanding the effects of environmental contaminants on honeybees is essential to minimize their impacts on these important pollinating insects. The aim of this study was to assess the ecotoxicological status of honeybees in environments undergoing different anthropic pressure: a wood (reference site), an orchard, an agricultural area, and an urban site, using a multi-biomarker approach. To synthetically represent the ecotoxicological status of the honeybees, the responses of the single biomarkers were integrated by the Integrated Biological Response (IBRv2) index. Overall, the strongest alteration of the ecotoxicological status (IBRv2 = 7.52) was detected in the bees from the orchard due to the alteration of metabolic and genotoxicity biomarkers indicating the presence of pesticides, metals, and lipophilic compounds. Honeybees from the cultivated area (IBRv2 = 7.18) revealed an alteration especially in neurotoxicity, metabolic, and genotoxicity biomarkers probably related to the presence of pesticides, especially fungicides. Finally, in the urban area (IBRv2 = 6.60), the biomarker results (GST, lysozyme, and hemocytes) indicated immunosuppression in the honeybees and the effects of the presence of lipophilic compounds and metals in the environment.

Festuca valesiaca Schleich. ex Gaudin newly discovered in the Central Apennines (Italy): a further example of steppe relict in the Abruzzo “dry valleys” - Goffredo Filibeck; Laura Cancellieri; Fabrizio Bartolucci; Ute Becker; Fabio Conti; Samuele Maestri; Marlene Mürz; Elena Schommer; Marta G. Sperandii; Thomas Becker (Plant Biosystems, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Calcium/calmodulin-stimulated adenylyl cyclases 1 and 8 regulate reward-related brain activity and ethanol consumption - Kelly E. Bosse; Farhad Ghoddoussi; Ajay T. Eapen; Jennifer L. Charlton; Laura L. Susick; Kirt Desai; Bruce A. Berkowitz; Shane A. Perrine; Alana C. Conti (Brain Imaging and Behavior, 2019)

The starch-bound alpha-amylase/trypsin-inhibitors in Avena - Laura Gazza; Gloria Gazzelloni; Federica Taddei; Arianna Latini; Vera Muccilli; Michela Alfieri; Salvatore Conti; Rita Redaelli; Norberto E. Pogna (Molecular Genetics and Genomics, 2016)

Biochemical and molecular characterization of Avena indolines and their role in kernel texture - Laura Gazza; Federica Taddei; Salvatore Conti; Gloria Gazzelloni; Vera Muccilli; Michela Janni; Renato D’Ovidio; Michela Alfieri; Rita Redaelli; Norberto E. Pogna (Molecular Genetics and Genomics, 2015)

Mycophenolate mofetil in systemic lupus erythematosus: results from a retrospective study in a large monocentric cohort and review of the literature - Fabrizio Conti; Fulvia Ceccarelli; Carlo Perricone; Laura Massaro; Enrica Cipriano; Viviana Antonella Pacucci; Simona Truglia; Francesca Miranda; Francesca Morello; Cristiano Alessandri; Francesca Romana Spinelli; Guido Valesini (Immunologic Research, 2014)

Mapping protein signal pathway interaction in sarcoma bone metastasis: linkage between rank, metalloproteinases turnover and growth factor signaling pathways - Amalia Conti; Virginia Espina; Antonella Chiechi; Giovanna Magagnoli; Chiara Novello; Laura Pazzaglia; Irene Quattrini; Piero Picci; Lance A. Liotta; Maria Serena Benassi (Clinical & Experimental Metastasis, 2014)

Use of discriminant analysis in assessing pulmonary function worsening in patients with sarcoidosis by a panel of inflammatory biomarkers - Gregorino Paone; Alvaro Leone; Sandro Batzella; Vittoria Conti; Francesco Belli; Laura De Marchis; Alice Mannocci; Giovanni Schmid; Claudio Terzano (Inflammation Research, 2013)

Volatile chemical composition and bioactivity of six essential oils against the stored food insect Sitophilus zeamais Motsch. (Coleoptera Dryophthoridae) - Alessandra Bertoli; Barbara Conti; Valerio Mazzoni; Laura Meini; Luisa Pistelli (Natural Product Research, 2011)

From Pichia anomala killer toxin through killer antibodies to killer peptides for a comprehensive anti-infective strategy - Luciano Polonelli; Walter Magliani; Tecla Ciociola; Laura Giovati; Stefania Conti (Antonie van Leeuwenhoek, 2011)

Starch-bound 2S proteins and kernel texture in einkorn, Triticum monococcum ssp monococcum - Federica Taddei; Laura Gazza; Salvatore Conti; Vera Muccilli; Salvatore Foti; Norberto Edgar Pogna (Theoretical and Applied Genetics, 2009)

Transport and consumption rate of O2 in alginate gel beads entrapping hepatocytes - M. Cristina Annesini; Giuseppe Castelli; Filippo Conti; Laura Conti De Virgiliis; Luigi Marrelli; Alfredo Miccheli; Elisabetta Satori (Biotechnology Letters, 2000)

The effect of retinoic acid on the re-establishment of differentiated hepatocyte phenotype in primary culture - L. Falasca; Anna Favale; Annalucia Serafino; Carmen Ara; Laura Conti Devirgiliis (Cell and Tissue Research, 1998)